USE OF APICECTOMY IN PARENDODONTIC SURGERY: A narrative literature review - Gabriel de Lima, Elias (2024)
Parendodontic surgery is a procedure used in chronic cases of persistent periapical infection, in addition to cases of calcified root canals where conventional endodontic treatment has not been successful. This technique may be associated with apicoectomy for cases in which it is necessary to apicotomize a root, and is considered a very invasive procedure. Even so, it is a modality that receives great prominence among endodontic procedures, since it aims to remove bacteria present in the apical region, in addition to preventing other microorganisms from re-entering the apical tissues of the canal. Given the importance of this therapeutic technique, the present study aimed to discuss the impressions contained in the literature regarding the use of apicoectomy in parendodontic surgery, discussing its indications and importance in current clinical practice. The study was developed through a narrative review of the literature, with the selection of studies published between 2020 and 2024 and made available in the SCIELO, Publimed and Google Scholar databases. Based on the application of the research criteria, eight studies were selected, which reinforce the importance of endodontic surgery associated with apicoectomy as a highly efficient technique for cases of failure of conventional endodontic treatment. Through the selected studies, it was found that when indicated appropriately and executed correctly by professionals, this technique allows for efficient treatment. In addition, it is essential that professionals who perform this technique have the necessary knowledge and skills, in addition to the use of appropriate materials that can guarantee the best therapeutic results.